"On Water": Efficient Iron‐Catalyzed Cycloaddition of Aziridines with Heterocumulenes1. Issue 2 (20th November 2012) - Sengoden, Mani; Punniyamurthy, Tharmalingam
<x xml:space="preserve">Abstract</x> In suspension: The reaction of aziridines with heterocumulenes in the presence of Fe(NO3)3⋅9 H2O in aqueous suspension provides access to functionalized five‐membered heterocycles in good to high yields. This protocol has a wide substrate scope, is simple, and uses a nontoxic and cheap catalyst.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>